Urgensi Lembaga Adat Membentuk Karakter Patuh pada Masyarakat Melayu Sungai Abu Kerinci-Jambi - CENDRA, ALIR AGUS; Mahabbati, Suci; Rizal Ramdhani (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This research was conducted to explain and examine the urgency of customary institutions in forming obedient characters in the Malay community of Sungai Abu Kerinci-Jambi. The purpose of this study is to explain the existence of the customary existence of the Kerinci Malay community, legal compliance in the Kerinci Malay customary institution, the application of obedient character in the community, and the role of customary institutions in forming obedient character in the Kerinci-Jambi community. This research is a qualitative research because it formulates generalizations of the analyzed data based on the phenomena found. The descriptive-analytical method is the method used in this study. The results of this study show that the influence of customary law in the Kerinci Malay community provides awareness of compliance with customary law by the community. The implementation of the character of obedience to customary law and customary institutions in the Malay community of Sungai Abu Kerinci concerns all social activities of community life inhabiting the Malay customary territory of Sungai Abu Kerinci. Customary Institutions play an active role in shaping obedient character in the Malay indigenous people of Sungai Abu Kerinci. Indigenous institutions play a role in sheltering and channeling the aspirations of indigenous peoples; Serving the needs of indigenous peoples; Making a work program, namely regulating the work program of customary institutions for the community; Increasing public understanding, awareness and compliance with customary law; Making legal rules for people who violate the rules that have been set by custom and have been agreed upon by mutual agreement. These customary provisions are complied with and have become a form of the obedient character of the indigenous people of Sungai Abu Kerinci. This is an indicator that the cultivation of the character of obedience to customary law can be applied by the Malay customary institution of Sungai Abu Kerinci in the midst of its community.